2010
DOI: 10.1021/jp105629r
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Magnetic, and Electrically Conductive Graphene/Fe3O4 Paper and Its Application for Magnetic-Controlled Switches

Abstract: The emerging field of free-standing and flexible paperlike materials based on graphene sheets has become the focus of considerable research in recent years because of the scientific and technological significance of these materials. In particular, multifunctional flexible graphene-based films or papers are in high demand for various applications. Herein, we report the fabrication of magnetic, electrically conducting, and flexible paper composed of graphene and nanoscale Fe3O4 particles made using a simple yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(98 citation statements)
references
References 39 publications
1
97
0
Order By: Relevance
“…Graphite oxide (GO) was prepared from natural graphite by the modified Hummer's method [21,22]. The superparamagnetic Fe 3 O 4 -RGO nanosheets were prepared via solvothermal method with some modification of those reported literatures [23,24].…”
Section: Synthesis Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…Graphite oxide (GO) was prepared from natural graphite by the modified Hummer's method [21,22]. The superparamagnetic Fe 3 O 4 -RGO nanosheets were prepared via solvothermal method with some modification of those reported literatures [23,24].…”
Section: Synthesis Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…The synthesis of MRGO nanocomposites has been reported in the literature [32][33][34][35][36], but the methods involved are usually multistep or require some rigorous conditions and toxic, expensive raw materials. Previous work has shown that solvothermal reduction is an effective method of lowering the oxygen content and defect level in graphene sheets [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid carrier can be selected by seal medium and working conditions which can be water, kerosene, or silicone oil [2][3][4][5][6] .Because of the special physical properties, chemical properties and fluid properties of water-based magnetic fluids, they can be widely used in mechanical, chemical, medical and other fields [7] , especially in hyperthermia.…”
Section: Introductionmentioning
confidence: 99%